Fungal species associated with grapevine trunk diseases in Washington wine grapes and California table grapes, with novelties in the genera Cadophora, Cytospora, and Sporocadus - Travadon, Renaud; Lawrence, Daniel P.; Moyer, Michelle M.; Fujiyoshi, Phillip T.; Baumgartner, Kendra (Frontiers in Fungal Biology, 2022)
Grapevine trunk diseases cause serious economic losses to grape growers worldwide. The identification of the causal fungi is critical to implementing appropriate management strategies. Through a culture-based approach, we identified the fungal species composition associated with symptomatic grapevines from wine grapes in southeastern Washington and table grapes in the southern San Joaquin Valley of California, two regions with contrasting winter climates. Species were confirmed through molecular identification, sequencing two to six gene regions per isolate. Multilocus phylogenetic analyses were used to identify novel species. We identified 36 species from 112 isolates, with a combination of species that are new to science, are known causal fungi of grapevine trunk diseases, or are known causal fungi of diseases of other woody plants. The novel species Cadophora columbiana, Cytospora macropycnidia, Cytospora yakimana, and Sporocadus incarnatus are formally described and introduced, six species are newly reported from North America, and grape is reported as a new host for three species. Six species were shared between the two regions: Cytospora viticola, Diatrype stigma, Diplodia seriata, Kalmusia variispora, Phaeoacremonium minimum, and Phaeomoniella chlamydospora. Dominating the fungal community in Washington wine grape vineyards were species in the fungal families Diatrypaceae, Cytosporaceae and Sporocadaceae, whereas in California table grape vineyards, the dominant species were in the families Diatrypaceae, Togniniaceae, Phaeomoniellaceae and Hymenochaetaceae. Pathogenicity tests demonstrated that 10 isolates caused wood discoloration similar to symptomatic wood from which they were originally isolated. Growth rates at temperatures from 5 to 35°C of 10 isolates per region, suggest that adaptation to local climate might explain their distribution.